Hepatic encephalopathy due to extrahepatic portosystemic shunt - Sazumi, Yosuke (Clin Case Rep, 2020)
Clinicians should recognize extrahepatic portosystemic shunt as a cause of refractory or intermittent hepatic encephalopathy. Treatment strategies should be individualized according to patients' anatomic and hemodynamic status.